If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 2f + -10 + -8 Reorder the terms: -12 = -10 + -8 + 2f Combine like terms: -10 + -8 = -18 -12 = -18 + 2f Solving -12 = -18 + 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. -12 + -2f = -18 + 2f + -2f Combine like terms: 2f + -2f = 0 -12 + -2f = -18 + 0 -12 + -2f = -18 Add '12' to each side of the equation. -12 + 12 + -2f = -18 + 12 Combine like terms: -12 + 12 = 0 0 + -2f = -18 + 12 -2f = -18 + 12 Combine like terms: -18 + 12 = -6 -2f = -6 Divide each side by '-2'. f = 3 Simplifying f = 3
| 3j+(-8)=13 | | 1/3m^2-5/3m=1/3m | | -76=3x-6x+1 | | 9(k-1)=36 | | d-16+5d=14 | | y-(-1)=7/8(x-9) | | 3g+5=26 | | 2n+8=6n | | 0=4x^2+5x-2 | | 3x+2(x+6)=37 | | 6=3(3j-4) | | 6r^2-12r-20=-9 | | 12=4(2m+5) | | 4(2x+7)-8=60 | | -6(d+2)=12 | | -3(2+y)=48 | | 17x^2-13x-2=0 | | 7c-5d-6c+4d= | | 81m^2-64m^2/9x-8x | | y=-3x(-2) | | a(12+8)=54 | | (ax-12b)(ax+12b)= | | (-2xy)(-6x)= | | ax+x= | | (a-5x/2a)-(8a-3x/2a) | | 15+2(y+x)=37 | | Y^4+21y^2-72=0 | | X-(0.25*X)=27 | | 180=(180-(7x-4))+(7x-4) | | 600x-.5x^2-(100x+2x^2)= | | 2(0)+3(0)+z=6 | | 2(x)+3(0)+0=6 |